THE BULGARIAN SOCIALIST PARTY ON THE PATH TO DE-EUROPEANIZATION (Studia Politica. Romanian Political Science Review, 2025)
The article's main purpose is to shed light on the Euroscepticism of the Bulgarian Socialist Party (BSP) and its shifting identity towards European issues, liberal democracy, and in terms of party organization during the last decade. More than twenty years ago, the successor of the former Bulgarian Communist Party managed to achieve a difficult (and, it turns out, superficial) Europeanisation and Social-democratization. BSP supported the country's accession to the EU and the integration in NATO. Now, the party is identifiable as a pro-Russian actor, opposed to the Istanbul convention, spreading conservatism, and hysteria against the so called "gender ideology," fighting against economic neo-liberalism but also liberal ideas. The Russian war against Ukraine significantly impacted domestic politics and the structure of party competition, revitalizing the historic divide between pro-Russian and pro-Western camps. Isolated, the BSP lost its position as a major party of government and embraced anti-establishment and protest-party profile. The main research questions address the essence of the BSP's ethnonationalist and conservative turn, and its hybrid interpretations of "national interest" and "patriotism" in its discourses and documents. Special attention is paid to the BSP's positions towards the war in Ukraine. Our main approach is grounded on the path dependency theory and on the supply and demand sides of the fragmented party system.
Keywords: Bulgarian Socialist Party; path dependency; party change; Euroscepticism; Nationalism